Mengembangkan Kemampuan Berhitung Anak Usia Dini Melalui Kegiatan Bermain Stick Angka - Himmatul Farihah (SELING: Jurnal Program Studi PGRA, 2017)
: Results Preliminary observations indicate that learning in TK Tunas Harapan Brondong District of Lamongan is often less appealing to children. There are some things that cause this, including the presentation of a monotonous activities and media which are used as props less varied. activities to learn to count only use media board and fingers only. This greatly affects the poor performance beginning child to learn to count. Of the 22 children only 6 children who are already able to count some others still need the guidance of a teacher.This study aims to: 1) Describe the implementation of stick figures playing in efforts to improve the numeracy skills of children in group A at the beginning of TK Tunas Harapan Brondong District of Lamongan. 2) To describe the resulting increase in numeracy starters through play activities of children in group A stick figure in Subdistrict Brondong TK Tunas Harapan Lamongan.This research uses Action Research (PTK). Class action research model used is the model Kemmis and Mc Taggart, Kurt Lewin model development. Implemented through two cycles of action. Numeracy starters were developed in this study: (1) Referring to the order of objects to numbers 1-10 (2) Mention the epitome of numbers 1-10 (3) Sort emblem numbers 1-10. (4) Pair emblem with the number of objects up to 10. (5) Summing up the results of 10 numbers. The results showed that the action through play activities undertaken science can improve cognitive abilities in the first cycle increased by 27% to 54%, and in the second cycle increased again by 37% to 91%. Of the overall increase in numeracy before action until the beginning of the second cycle of 64%.